LINQ to Objects Using C# 4.0 - Magennis, Troy (Addison-Wesley Professional, 2010)
"For several years, Troy has been one of the key figures in the LINQ community. This comprehensive and well-written book serves as a compendium of the important wisdom and experience that he has accumulated through his years of studying LINQ and its uses."--Charlie Calvert, Microsoft C# Community Program Manager "LINQ is changing the way we think about working with data and, in many ways, also about programming in general. LINQ to Objects Using C# 4.0 is a thorough reference that teaches how to simplify many day-to-day tasks with data. It also gives you the foundations that are necessary to understand a wide range of fascinating applications of LINQ that will, no doubt, continue to appear over the next few years." - Tomas Petricek, Microsoft MVP and author of Real-World Functional Programming Your Complete Example-Rich Guide to Using and Extending LINQ to Objects and PLINQ Using LINQ to Objects, .NET developers can write queries over object collections with the same deep functionality that was once available only with SQL and relational databases. Now, for the first time, developers have a comprehensive and authoritative guide to applying LINQ to Objects in real-world software. Microsoft MVP Troy Magennis introduces state-of-the-art techniques for working with in-memory collections more elegantly and efficiently-and writing code that is exceptionally powerful, robust, and flexible. Drawing on his unsurpassed experience coding software using LINQ and hosting the popular HookedOnLINQ.com site, Magennis presents timely, realistic solutions to a wide spectrum of development challenges, such as combining data from multiple sources, and achieving optimal performance with extremely large sets of data. You'll begin with brief quick-starts that walk you through LINQ to Objects' key features and query syntax. Next, you'll drill down to detailed techniques for applying and extending these features with C# 4.0 and C# 3.0-including code examples that reflect the realities of production development. Coverage includes - Writing basic LINQ queries with C#: filtering, projecting, and sorting data from in-memory collections - Mastering advanced techniques for grouping and joining data and understanding the performance implications of each technique - Taking full advantage of LINQ's standard query operators - Creating custom query operators that follow best practices for coding patterns and error handling - Writing more fluent, readable LINQ qu ...